2015
DOI: 10.1016/j.foodchem.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the relationships among proteolysis, lipid oxidation, structure and texture throughout the dry-cured ham process

Abstract: Temperature, salt and water contents are key processing factors in dry-cured ham production. They affect how proteolysis, lipid oxidation, structure and texture evolve, and thus determine the sensory properties and final quality of dry-cured ham. The aim of this study was to quantify the interrelationships and the time course of (i) proteolysis, (ii) lipid oxidation, (iii) five textural parameters: hardness, fragility, cohesiveness, springiness and adhesiveness and (iv) four structural parameters: fibre number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 41 publications
10
46
2
5
Order By: Relevance
“…Ruiz-Ramirez et al [16] showed that proteolysis index (degree of proteolysis) which is calculated as the percentage of nonprotein nitrogen divided by total nitrogen was 25 and 18 %, respectively, for Biceps femoris and Semimembranosus muscle (10 months of manufacturing). Similar results were obtained by Buscailhon et al, Flores et al and Harkouss et al [47][48][49].…”
Section: Muscle Characteristics and Compositionsupporting
confidence: 90%
See 4 more Smart Citations
“…Ruiz-Ramirez et al [16] showed that proteolysis index (degree of proteolysis) which is calculated as the percentage of nonprotein nitrogen divided by total nitrogen was 25 and 18 %, respectively, for Biceps femoris and Semimembranosus muscle (10 months of manufacturing). Similar results were obtained by Buscailhon et al, Flores et al and Harkouss et al [47][48][49].…”
Section: Muscle Characteristics and Compositionsupporting
confidence: 90%
“…Skrlep et al [80] also found for "Kraski prsut" dry-cured ham that a lower pH of the raw meat (from 5.51 to 5.63) had a positive effect on proteolysis compared to higher pH (from 5.80 to 6.18). This occurred due to the increased cathepsin activity at lower pH, which affects the extent of proteolysis [16,49,81,82]. Morales et al [77] also showed that proteolysis index decreased from 19.3 to 16.7 % when the salt concentration increased from 1 to 4 %.…”
Section: Activity Of Proteasesmentioning
confidence: 99%
See 3 more Smart Citations